THE EXISTENCE OF THE DHIDDUL BATHIL BELIEFS IN AEK TAPUS SIHEPENG VILLAGE, SIABU SUBDISTRICT, MANDAILING NATAL DISTRICT - Lubis, Sufrin Efendi (IAIN Palangka Raya, 2023)
This research aims to describe the existence of the Dhiddul Bathil belief system which is centered in Desa Aek Tapus Sihepeng, Kabupaten Mandalingi Natal, North Sumatra. The Dhiddul Bathil belief system can be called a local belief system that is on the verge of extinction. This flow of belief faced quite intense shocks, not only by the surrounding community, the problematic crisis also emerged from within themselves. This research uses qualitative methods and data sources come from observations and interviews as well as other literature related to the research theme. The results of the research show that this belief is currently facing a crisis in various aspects that are almost on the verge of extinction. This crisis was caused by at least two things. 1). Internal problems that lead to division and conflict. This phenomenon has implications for decreasing the quantity and loyalty of adherents and followers. 2). There are attempts by certain groups to discredit this flow in the eyes of the younger generation